Toxicity Test of Elo (Ficus Racemosa L.) Leaf Extracts and Fractions Using Brine Shrimp Lethality Test Methods - Suryani, Novia; Gustiana, Serli (Al-Kimia, 2023)
This study aims to determine the toxicity ability of the Ficus racemosa L. plant, known as the elo plant, which has been widely applied as an alternative medicine for natural ingredients. The use of natural ingredients as drug candidates is one option to increase the value of natural ingredients and become biodiversity in Indonesia. The research method used is the maceration method used to obtain leaf extract. Furthermore, the extract obtained was partitioned using n-hexane, ethyl acetate, and chloroform solvents to obtain the leaf fraction. Qualitative tests were carried out to determine the secondary metabolite compounds. Meanwhile, the toxicity ability of elo plant extract and leaf fraction was tested using the Brine Shrimp Lethality Test (BSLT) as an initial toxicity screening with Artemia salina Leach. Based on the results, revealed the extract and fraction of the leaves contained secondary metabolites in the form of flavonoids, alkaloids, and saponins. Toxicity test obtained LC50 value of leaf extract of 91.76 ppm; leaf n-hexane fraction of 220.47 ppm; leaf ethyl acetate fraction of 249.13 ppm; and leaf chloroform fraction of 338.16 ppm. Based on the LC50 value, it reveals that the leaf extract and leaf fraction of the elo plant perform toxic potency.